Vedolizumab Serum Trough Concentrations and Response to Dose Escalation in Inflammatory Bowel Disease - Vaughn, Byron P. (J Clin Med, 2020)
Serum vedolizumab concentrations are associated with clinical response although, it is unknown if vedolizumab concentrations predict response to dose escalation. The aim of this study was to identify if vedolizumab trough concentrations predicted the response to vedolizumab dose escalation. We assessed a retrospective cohort of patients on maintenance vedolizumab dosing at five tertiary care centers with vedolizumab trough concentrations. Multivariate logistic regression was used to control for potential confounders of association of vedolizumab concentration and clinical status. Those who underwent a dose escalation were further examined to assess if vedolizumab trough concentration predicted the subsequent response. One hundred ninety-two patients were included. On multivariate analysis, vedolizumab trough concentration (p = 0.03) and the use of immunomodulator (p = 0.006) were associated with clinical remission. Receiver operator curve analysis identified a cut off of 7.4 μg/mL for clinical remission. Of the fifty-eight patients with dose escalated, 74% of those with a vedolizumab concentration <7.4 μg/mL responded versus 52% of those with a vedolizumab trough concentration ≥7.4 μg/mL (p = 0.08). After adjustment for relevant confounders, the odds ratio for response with vedolizumab concentration <7.4 μg/mL was 3.7 (95% CI, 1.1–13; p = 0.04). Vedolizumab trough concentration are associated with clinical status and can identify individuals likely to respond to dose escalation. However, a substantial portion of patients above the identified cut off still had a positive response. Vedolizumab trough concentration is a potentially helpful factor in determining the need for dose escalation in patients losing response.